KAJIAN PENERAPAN GREEN PROCUREMENT PADA PROYEK INFRASTRUKTUR JALAN DI PROVINSI NUSA TENGGARA TIMUR - Messah, Yunita A.; Utomo, Sudiyo; Ballo, Angelica S. C. (Jurnal Teknik Sipil, 2016)
The issue of global warming and climate change is an environmental issue that the world's problems. Countermeasures are now established is sustainable development. One factor supporting sustainable development is an alternative device in the areas of procurement, that is green procurement. Determining the winner of the procurement system is noticed additional aspects, namely social, economic and environmental which in practice is still not determined the weight of each of the environmentally friendly aspects. The purpose of this study was to determine the weighting of the criteria for selecting a winner in the green procurement system and determine the relationship between environmental criteria. Data analysis technique using Analytical Network Process, in order to obtain a priority basis and weighting of each criterion so that it can be described the relationship between the criteria. The results of the study in the opinion of all respondents consisting of qualified contractors large and medium enterprises as well as the Procurement Services Unit predominant aspects in the procurement of environmentally friendly is a social aspect to the criteria that affect the human resources with the weight percentage is 10.40%. In these criteria there are sub-criteria that support namely the availability of experts and skilled workers, the availability of experts and skilled workers by level of education and experience as well as working procedures with the weight percentage of each sub-criteria 33,33%.